Scientific Advice to Governments: A Comparative Perspective Based on the Italian Experience During the Covid-19 (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Scientific advice to governments is an ancient practice, yet it is only in the second half of the twentieth century that we observe the gradual institutionalisation and proliferation of bodies established for this purpose. This development has been driven by the increasingly technical nature of the issues on which public decision-makers must act, including energy policy, genetically modified organisms (GMOs), bioethics, climate change and artificial intelligence. The Covid-19 pandemic placed scientific advisory bodies at the centre of government decision-making to an unprecedented degree, exposing both their structural strengths and limitations. Against this backdrop, this article takes a comparative approach, drawing on the Italian experience in particular, to analyse how scientific advice operates in times of crisis. This exploration provides a critical perspective through which to reconsider the institutional design, legitimacy, and operation of scientific advice in contemporary democracies, and to reflect on the evolving relationship between science and political decision-making.
Keywords: science advice; evidence-based policy; Covid-19; law and science